On basic Horn hypergeometric functions H3 and H4 - Shehata, Ayman (Advances in difference equations, 2020)
The purpose of this work is to demonstrate several interesting contiguous function relations and q -differential formulas for basic Horn hypergeometric functions H 3 and H 4 . Some properties of our main results are also constructed.